SATISFACTION OF MIDWIVES WITH THE USE OF THE MIDWIFERY EMERGENCY GUIDE APPLICATION IN THE ISLANDS (SI-PK3) AS AN INNOVATION FOR MANAGING MATERNAL EMERGENCY CASES IN THE KEPULAUAN RIAU PROVINCE IN 2023 - Saputri, Nurul Aini; Melly Damayanti; Vina Jayanti; Ika Susanti (International Journal of Social Science, 2024)
One of the initiatives to reduce MMR is to have health staff who are competent in emergency management, given the hurdles and challenges that exist on the islands. Island referral paths typically use both land and maritime routes. This study attempted to assess respondents’ satisfaction with the trial usage of si-PK3 as a midwife guide in addressing maternal crises on the islands. This research was quantitative research. Respondents were given one month to utilize the PK3 application. After one month, respondents were given a questionnaire measuring their happiness with the program using the End User Computing happiness (EUCS) approach. As a whole, the level of user satisfaction with the PK3 Application is 3.14, which was at level 4 (satisfied), indicating that the PK3 Application was generally regarded as satisfactory.